ELEMENTAL ABUNDANCES IN THE ATMOSPHERES OF THREE METAL - DEFICIENT GIANTS - Mishenina, T. V.; Klochkova, V. G.; Panchuk, V. E. (Одеські астрономічні публікації, 2017)
High dispersion high resolution CCD spectra have been used for the determination of the elemental abundances in three metal-deficient stars. The following results were obtained: 1) an overabundance of O is found; 2) Si, Ca, Ti are overabundant with respect to iron in stars with [Fe/H]= -1.5; 3) halo stars show an underabundance of the odd elements Na and Al relative to the abundance of the even element Mg; 4) Ni and Mn are slightly over deficient; 5) an underabundance of Cu is found in all three stars ; 6) s-process elements are slightly overabundant.